PYELOPLASTY IN BIFID RENAL PELVIS WITH OBSTRUCTION OF THE LOWER MOIETY - Petrovski, Mile; Todorovikj, Lazar; Aleksovski, Zlatko; Tanev, Aleksandar; Coklevska, Natalija (Journal of Morphological Sciences; Vol 4 No 3 (2021): JMS, 2021)
Duplications in the urinary collecting system and pyeloureteral junction obstruction (PUJO) are common, but the simultaneous presence of both anomalies is rarely encountered. In duplicate incomplete systems, PUJO usually affects the lower moiety of the kidney. We present a case of a 2- year old boy with left bifid renal pelvis and hydronephrosis of the lower moiety of the kidney. Keywords: pyeloplasty, bifid renal pelvis, hydronephrosis, Anderson Hynes. https://doi.org/10.55302/JMS2143058p